Oiceoptoma tangi (Coleoptera: Silphidae: Silphinae), a new species of carrion beetle from eastern China - Sommer, David; Růžička, Jan; Nishikawa, Masaaki; Schneider, Jan (Zootaxa, 2021)
A new species, Oiceoptoma tangi Sommer, Růžička, Nishikawa & Schneider, new species, from Zhejiang Province, China, is described and illustrated. The new species is closely related to O. subrufum (Lewis, 1888), distributed in Central and North-eastern China, the Korean Peninsula, Far East of Russia and Japan, and to O. nigropunctatum (Lewis, 1888), endemic to Japan. All three species are keyed, and distribution maps of all three species are presented.